Chemical Constituents Isolated From Leaves Of Barleria Cristata Linn. - K. HEMALATHA; N. HAREEKA; D. SUNITHA (International Journal of Pharma and Bio Sciences, 2012)
Two phenolic compounds (P- Coumaric acid and α–Tocopherol), two flavonoidal compounds ( luetoline and 7-methoxy luetoline) and two iridoidal glycosides (barlerin and schanshiside methyl ester) have been isolated from leaves of Barleria cristata their structure were established by spectral analysis. This is the first report of occurrence of these compounds from Barleria cristata Linn plant.